Rancang Bangun Mesin Poles Piringan Tunggal (Single Disc) Untuk Proses Metalografi - Ferry Budhi Susetyo; Muhamad Muslih; Muhamad Agil Febrianto; Basori Basori (Universitas Nasional, 2021)
A polishing machine for the metallographic process is the equipment used to carry out surface preparations. The smooth surface is expected so that after etching it can be seen the micro or macrostructure of a material being studied with the aid of a microscope. In this research, we design and manufacture polishing machines. The main materials used in the process of designing this polishing machine are an electric motor (AC), carbon steel, cables, contactors, stainless steel plates, pushbuttons, emergency buttons, potentiometers, v belts, pulleys, bearings, hoses, and shafts. This method of the research process begins with calculating the diameter of the follower pulley, then continues with size planning, drawing work, making simple electrical wiring drawings, manufacturing components, and assembling and testing. This polishing machine for the metallographic process has been designed as a disk rotating speed of 600 rpm, an electric motor of 135W with a voltage of 220V, and also has a plumbing system. From the test results of polishing machine for metallography, the desired polishing results were obtained.